Study on effective parameter of the triple-pressure reheat combined cycle performance - Thamir K., Ibrahim; M. M., Rahman (Thermal Science, 2013)
The thermodynamic analyses of the triple-pressure reheat combined cycle gas turbines with duct burner are presented and discussed in this paper. The overall performance of a combined cycle gas turbine power plant is influenced by the ambient temperature, compression ratio and turbine inlet temperature. These parameters affect the overall thermal efficiency, power output and the heat-rate. In this study a thermodynamic model was development on an existing actual combined cycle gas turbine (CCGT) (In this case study, an effort has been made to enhance the performance of the CCGT through a parametric study using a thermodynamic analysis. The effect of ambient temperature and operation parameter, including compression ratio and turbine inlet temperature, on the overall performance of CCGT are investigated. The code of the performance model for CCGT power plant was developed utilizing the THERMOFLEX software. The simulating results show that the total power output and overall efficiency of a CCGT decrease with increase the ambient temperature because increase the consumption power in the air compressor of a GT. The totals power of a CCGT decreases with increase the compression rate, while the overall efficiency of a CCGT increases with increase the compression ratio to 21, after that the overall efficiency will go down. Far there more the turbine inlet temperature increases the both total power and overall efficiency increase, so the turbine inlet temperature has a strong effect on the overall performance of CCGT power plant. Also the simulation model give a good result compared with MARAFIQ CCGT power plant. With these variables, the turbine inlet temperature causes the greatest overall performance variation.